Assessing microcredit's role in enhancing economic well-being among low-income individuals in Sub-Saharan Africa - Sarkodie, Eric Effah; Maloma, Ismael (Asian Journal of Economic Modelling, 2025)
The study assesses the impact of microcredit on the economic welfare of low-income households across SSA from 2009 to 2019. The study used econometric methods, including panel regression models and the Generalized Method of Moments (GMM), to evaluate microcredit's role in enhancing economic well-being among low-income individuals in SSA. The choice of GMM was to address potential endogeneity. The results demonstrated the effectiveness of microcredit in alleviating poverty. The findings suggest that poverty reduction strategies should incorporate microcredit alongside improvements in education, infrastructure, and healthcare to achieve optimal outcomes. The study also identified education, population growth, per capita GDP, and transformed agriculture as critical factors in ensuring microcredit's effectiveness in improving economic well-being among low-income individuals in SSA. Microcredit is a valuable tool for enhancing economic well-being among low-income populations. Governments, financial institutions, and stakeholders must make deliberate efforts to sustain and expand microcredit in impoverished environments. Microcredit has the potential to address the low-income syndrome in SSA and reduce income inequality across social classes.